Generations : academic feminists in dialogue - Kaplan, E. Ann; Looser, Devoney, 1967- (Minneapolis : University of Minnesota Press, 1997)
Composed of essays from academic women at various professional stages-from established scholars to junior professors to graduate students-this collection illuminates the debates of feminist histories and future legacies, while analyzing the challenges of "passing the torch."
Introduction 1 : An exchange / E. Ann Kaplan and Devoney Looser -- Introducton 2 : Two essays -- Feminism, aging, and changing paradigms / E. Ann Kaplan -- Gen X feminists? Youthism, careerism, and the Third Wave / Devoney Looser -- Sisters are doing it to themselves / Diane Elam -- Generational difficulties ; or, the fear of a barren history / Judith Roof -- Black female spectatorship and the dilemma of tokenism / Michele Wallace -- Talking across / Jane Gallop and Elizabeth Francis -- Feminist psychology at thirtysomething : feminism, gender, and psychology's ways of knowing / Jeanne Marecek -- Shifting locations : Third World feminists and institutional aporias / Mona Narain -- Jason dreams, Victoria works out / Nancy K. Miller -- An open letter to institutional mothers / Rebecca Dakin Quinn -- Dancing through the mother field : on aggression, making nice, and reading symptoms / Lynda Zwinger -- Working mother / Ruthe Thompson -- "Somewhere in particular" : generations, feminism, class conflict, and the terms of academic success / Linda Frost -- The objectification of Julia : texts, textures, and contexts of black women in American television situation comedies / Angela M.S. Nelson -- When feminism met postfeminism : the rhetoric of a relationship / Jane Kalbfleisch -- Feminist misogyny ; or, what kind of woman are you? / Theresa Ann Sears -- Three feminist mother-daughter pairs in the nineteenth-and early-twentiteth-century United States / Barbara A. White -- Fissuring time, suturing space : reading Bharati Mukherjee's The holder of the world / Gita Rajan -- The anxiety of affluence : movements, markets, and lesbian feminist generation(s) / Dana Heller -- Feminist family values : or, growing old-and growing up-with the women's movement / Judith Newton.
Comprised of original essays presented at various conferences held between 1993 and 1996.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Feminism and education -- United States; Feminist theory -- United States; Universities and colleges -- United States -- Sociological aspects; Women college students -- United States -- Social conditions; Women college teachers -- United States -- Social conditions; Féminisme et éducation -- États-Unis.; Féminisme -- Philosophie -- États-Unis.; Professeures (Enseignement supérieur) -- États-Unis -- Conditions sociales; Étudiantes -- États-Unis -- Conditions sociales; Universités -- États-Unis -- Aspect sociologique; Théorie féministe -- États-Unis.; SOCIAL SCIENCE -- Feminism & Feminist Theory; Feminism and education; Feminist theory; Universities and colleges -- Sociological aspects; Women college students -- Social conditions; Women college teachers -- Social conditions; United States; Akademikerin; Feminismus; USA; Aufsatzsammlung